Subjective approach towards welfare understanding in the dolphin assisted therapy: experiences of families in pilot research - Kreivinienė, Brigita; Kleiva, Žilvinas (Social Welfare: Interdisciplinary Approach, 2017)
The article deals with a subjective approach towards the welfare of humans and dolphins perceived in the dolphin assisted therapy. Dolphin assisted therapy (DAT) is a therapy based on both-sided collaborative communication between child and dolphin. A pilot research of subjective welfare understanding is presented in the article. Eight families raising children with disabilities (one family with a child with cerebral palsy, two families with children with Down syndrome, and five families with children with autism spectrum disorder) took part in the dolphin-human welfare research. The research was carried out using a research strategy of triangulation applying different methods. The research was carried out using Portable Eye tracking system (SMI REDnScientific), Facial expression recognition software (Noldus Facereader 6.1), Event logging software for observational data collection, analysis and presentation with physiological data synchronization capabilities (Noldus Observer XT 12.5), qualitative telephone interview a week before the session of dolphin assisted therapy, open form for evaluation of the results of dolphin assisted therapy in a child one month later after the participation in DAT. The results brought to the light that the families were mostly happy when watching their children; families raising children with severe disability were most satisfied with the dolphin assisted therapy; the subjectively perceived welfare of dolphins was understood as a possibility to choose a child for communication; also, if the therapy goals were measurable, the more satisfying results were reflected by parents after a month after the dolphin assisted therapy program.